The Effectiveness of the Lok-R Model in Enhancing Academic Achievement in the Islamic Religious Education Study Program - Mukhlis Mukhlis; Nuril Huda; Dina Hermina (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2024)
This study aims to analyze the effectiveness of using the LOK-R Model in improving academic performance in the Islamic Education Study Program at Al-Jami Islamic College Banjarmasin. The research reveals how mastering academic material hinges on the application of the Lok-R Model. Through in-depth analysis, the study presents concrete evidence of improvements in the quality of learning and student achievements. The LOK-R Model, the primary focus of this research, paves the way to academic excellence through an innovative approach. Findings indicate that consistent application of this Model can enhance material understanding, student engagement, and ultimately, higher learning outcomes. The research utilizes N-Gain Score Analysis with data collection techniques involving Pre-Test and Post-Test. Results show that implementing the LOK-R Model significantly improves student learning outcomes. Additionally, students who participate in learning with the LOK-R Model also demonstrate improvements in literacy skills, orientation, collaboration, and reflection in understanding the material. The study underscores the need for integrating the LOK-R Model into higher education in Indonesia to help students develop skills relevant to contemporary demands. Research findings reveal a significant increase in average test scores, with a classical test result of 50% in the pre-test rising to 72.5% in the post-test, and an N-Gain Score percentage of 0.59 for the first subject matter increasing to 0.78 for the second subject matter. Therefore, the implementation of LOK-R is considered successful in enhancing student learning achievements, as it has met the success indicator of 75% in a classical sense. Individually, the average performance of students in the course has reached a minimum score of 70.